Mixed matrix membrane tip extraction coupled with UPLC–MS/MS for the monitoring of nonsteroidal anti-inflammatory drugs in water samples - Ganesan, Thipashini; Mukhtar, Nurul Hazirah; Lim, Hong Ngee; See, Hong Heng (MDPI, 2020)
An ultra-performance liquid chromatography–tandem mass spectrometry (UPLC–MS/MS) method, in combination with a mixed matrix membrane microextraction method for the quantification of nonsteroidal anti-inflammatory drugs (NSAIDs) in environmental water samples, is reported. The extraction device was prepared by casting well-dispersed polymeric bonded octadecyl (C18) particles in a cellulose triacetate matrix solution onto commercially available 200 μL micropipette tips. The membrane formed contains 25% of the adsorbent loading amount and was firmly attached to the inner wall of the membrane tip. The dynamic extraction was performed by withdrawing and dispensing the sample solution through the tip device for effective analyte adsorption, followed by the analyte desorption process into 40 μL of methanol and acetonitrile (1:1) prior to UPLC–MS/MS analysis. NSAIDs—namely diclofenac, ibuprofen, indoprofen, naproxen and sulindac—were chosen as targeted analytes. Several extraction parameters were comprehensively optimized, including sample pH value, ionic strength, dynamic extraction cycle, desorption solvent and desorption time. The optimized conditions demonstrated a linear range from 0.25 to 500 ng L−1, with correlation coefficients (r2) from 0.9988 to 0.9992 and detection limits ranging from 0.08 to 0.40 ng L−1. The recoveries of the spiked water samples were between 92% and 99% and exhibited excellent precision relative to standard deviations (RSDs ≤ 4.9%), and enrichment factors (EFs) were at 201–249 for the developed approach.